Kompetensi Profesionalisme Guru Terhadap Hasil Belajar Siswa Berfikir Kritis di SMP Negeri 35 Medan - Bima Pandawa Sinurat; Carlo Munthe; Dana Diva Ivan De La Pena Ginting; Innes Ferancia Damanik; Muhammad Izhar Tumanggor; Petrus Medikson Pardede; Vany Helpiana Saragih; Sri Yunita; Jamaludin Jamaludin (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
The mini research assignment of group 3 of the PPKn Reguler B 2023 class is entitled “The competence of teacher professionalism on student learning outcomes in critical thinking at SMP NGERI 35 Medan”. This study aims to examine the level of teacher professionalism, students' critical thinking skills, and the effect of teacher professionalism on students' critical thinking skills at SMP Negeri 35 Medan. The background of this study is based on the dominance of conventional learning methods used by teachers, where the learning process is more teacher-centered and does not encourage students to think critically. In addition, the limited use of interesting learning media and the lack of innovation in teaching approaches are also factors that influence students' low critical thinking skills. Through a qualitative research method with a descriptive approach, data was collected through interviews, observations, and documentation studies. The results showed that teacher professionalism plays an important role in creating a learning environment that supports the development of students' critical thinking. Teachers who apply varied learning strategies, such as group discussions, simulations, and the use of interactive media, are able to increase students' involvement in learning and encourage them to be more active in analyzing and solving problems. This research provides insights for schools and educators in developing more innovative learning strategies to improve students' critical thinking.